Stay in the light - Shine, A. M. (Head of Zeus, an Aries book, 2024)
The sequel to THE WATCHERS, now adapted into a major motion picture produced by M. Night Shyamalan from critically acclaimed Irish horror writer A.M. Shine. Mina knows the Watchers' power is growing. She flees for her life, but when she reports her fears she finds her sanity questioned. Can she convince people that the Watchers are real, and ready to strike - or will she suffer the fate she has dreaded since she first encountered those malevolent beings?